THE NON-RECIPROCITY OF CULTURAL-ECOLOGICAL RESILIENCE IN EASTERN SUMBA - Wohangara, B. Retang (UI Scholars Hub, 2025)
Resilience is one key concept of culture and ecology. It highlights a particular system's adaptive and thriving capacities in facing various challenges. This research-based article investigates the reciprocity of cultural-ecological resilience in three traditional communities in Eastern Sumba. It starts with the examination of cultural resilience and ecological resilience using five and seven qualitative indicators, respectively. The last part of the discussion analyzes how culture and ecology reciprocate in the given communities. The research employs a descriptive qualitative method. Data are collected by conducting mini-ethnographic field research for interviews, documentation, and focus group discussions. Using the five and seven indicators to examine cultural resilience and ecological resilience respectively, the research reveals that the communities are generally culturally resilient, yet ecologically vulnerable. The culture and ecology of the three traditional communities are non-reciprocal. Traditional communities require empowerment through collaborations to transform their ecological spirituality into tangible actions to build cultural-ecological resilience.